STATE POLICY IN THE FIELD OF PREVENTION AND COUNTERACTION TO CYBERTHREATS – EXPERIENCE OF THE REPUBLIC OF POLAND - Hranovskyi , Mykola (Theory and Practice of Public Administration, 2019)
In today’s world there is a tendency for a significant increase in the number of cyber threats and attacks that are becoming more sophisticated and unpredictable. Ensuring cybersecurity is extremely important for Ukraine in conditions of a hybrid war. The Law of Ukraine on Cybersecurity and further development of international cooperation in the field of cyberspace protection with the United States and the European Union is more urgent than ever. It is necessary to improve international mechanisms and a common international policy to develop and implement effective methods for combating cyber threats. For attention offers a concise analysis of actions aimed at preventing and counteracting cyber threats through the example of the Republic of Poland. Ensuring cybersecurity in Europe, in particular in Poland, and building a sustainable cyber-threat system –is a continuous process and a long-standing process that needs to be joined by Ukraine as a full partner. Considering the Polish experience and the experience of international partners, it is proposed to address the issues of improving the system of work of the existing information security structures in Ukraine, as well as to consider the creation of additional profile structures at the level of central executive authorities, as well as target groups based on newly created agencies and scientific and research institutions for further work in the field of cybersecurity and improvement of public administration; digitalization and development of the electronic communications industry; definition of a promising organizational and technical model of cyber defense and improvement of cybersecurity education, etc. In today’s context, the information component is gaining more weight and becoming one of the most important elements of national security.